PERTANGGUNGJAWABAN HUKUM TERHADAP NOTARIS YANG MEMBUKA KANTOR CABANG ATAS NAMA SENDIRI (PUTUSAN NOMOR : 2/PTS/Mj.PWN.DKIJakarta/xi/2017) - Febry Yanti; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2019)
Indonesia is a country that adheres to the legal system. The role of the notary is very important in Indonesia. Notaries act as public officials in providing legal services to the public. Notaries are public officials who have the authority to make authentic deeds. A notary position is a public or public position because a notary is appointed and dismissed by the government. Notaries are prohibited from opening more than one notary office because notaries can only open one notary office. But in reality there is a notary who opens a branch office. How the accountability and position of the notary who establishes a branch office on its own behalf is a problem discussed. The research method used is normative legal research is to find the truth of coherence, namely the rule of law in accordance with legal principles. sourced from primary data and secondary data as other supporting data which are analyzed quantitatively. The results of the study explained that the West Jakarta Regional Supervisory Board found that there was a notary office with 2 signboards in the West Jakarta area that had a notary office named Notary Netty Maria Machdar. So that Netty Maria Machdar was found guilty and the position of the notary became hanging due to the absence of a further verdict because it was only proposed to be honorably dismissed by the Regional Supervisory Board so that in this case Netty Maria Machdar was found guilty and obliged to replace the loss but because there was no further verdict. Notary Netty Maria Machdar can still use her rights as a legitimate Notary. Notary Netty Maria Machdar also violated the Indonesian Notary Association Code of Ethics.